Perancangan Aplikasi Game Olahraga Tradisional Untuk Anak Sekolah Dasar Menggunakan Macromedia Flash - Rizka Tri Alinse, Rizka Tri; Kalsum, Toibah Umi (Jurnal Media Infotama, 2020)
Traditional sports games can be used to introduce elementary school students to better understand how to play and the concept of the origin of the game itself. So that traditional games, especially traditional sports games, will be preserved and remain known in society. The aim of this research is to design a traditional game application for elementary school children using Macromedia Flash 8. The method used in this research is a system development method that implements the design into a form of traditional sports game application design for elementary school children. This traditional sports game application can be further developed in terms of design and also in terms of function. With this traditional sports game application, elementary school students can better understand and comprehend what and how the traditional long jump sports game is played.